Socio-Philosophical Features Of Ensuring The Interests Of Youth In Society (Czech Journal of Multidisciplinary Innovations, 2025)
This article covers scientific issues of interests in society, their emergence and improvement, and their significance in the process of development of the system of needs and interests in man and society. In particular, the article provides a socio-philosophical analysis of the priority aspects of the interests of young people in the social life of society, important aspects of their implementation in social practice